2005
DOI: 10.1038/sj.ijir.3901338
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of erection after pelvic urologic surgery: our experience

Abstract: The incidence of erectile dysfunction (ED) in patients undergoing pelvic urologic surgery, the efficacy and tolerability of vardenafil-based rehabilitative treatment as first option in these patients, the role of spontaneous erection (SE) as a possible positive predictive factor to erection recovery after such treatment, and the role of second-line therapies in those nonresponders are evaluated. All the patients undergoing pelvic urologic surgery at our Institution between November 2002 and December 2003 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Also, the role of early use of PDE5 inhibitors appears to give minimal to moderate benefit in early ED. This benefit appears to be a 20% increase at 1 year in erection function, defined by vaginal penetration [23][24][25]. Combination therapy using intracavernous injections and sildenafil facilitated early sexual intercourse, patient satisfaction, earlier return of spontaneous erections and potentially an earlier return of natural erections sufficient for vaginal potency.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the role of early use of PDE5 inhibitors appears to give minimal to moderate benefit in early ED. This benefit appears to be a 20% increase at 1 year in erection function, defined by vaginal penetration [23][24][25]. Combination therapy using intracavernous injections and sildenafil facilitated early sexual intercourse, patient satisfaction, earlier return of spontaneous erections and potentially an earlier return of natural erections sufficient for vaginal potency.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative nocturnal penile tumescence assessments were supportive. In 2005, Gallo and colleagues [72] evaluated the role of vardenafil in the recovery of erectile function following pelvic urologic surgeries (RRP and cystectomy). After 6 mo of daily therapy, vardenafil therapy increased the mean IIEF-5 score to 12.9 points in the BNS group, to 8.0 points in the UNS group, and to 11.3 points in the BNS radical cystectomy group.…”
Section: Pharmacological Prevention Of Erec-tile Dysfunction After Ramentioning
confidence: 99%
“…In a subset of 54 patients (35 sildenafil group, 19 control group) from the same study, longitudinal measurement of nocturnal penile tumescence and rigidity evaluation revealed that 29% (10/35) of the sildenafil group demonstrated return of spontaneous erectile function compared to 5% (1/19) in the control group. 22 They also reported that tip rigidity of 455% appears to be the most important parameter to discriminate between responders and non-responders.…”
Section: Role Of Oral Medications In Early Penile Rehabilitationmentioning
confidence: 99%
“…Recently, Gallo et al 22 from Italy evaluated the role of vardenafil in the recovery of erectile function following pelvic urological surgeries (RP and cystectomy). 23 After 6 months, vardenafil therapy increased the mean International Index for Erectile Function-5 (IIEF-5) score of 12.9 points in bilateral nerve-sparing RP patients, of 8.0 points in unilateral nerve-sparing RP patients and of 11.3 points in nerve-sparing radical cystectomy patients.…”
Section: Role Of Oral Medications In Early Penile Rehabilitationmentioning
confidence: 99%